Translating management research into practice: a six-step path to engage stakeholders - York, John M.; Turner, Neil; Wilson, Grant Alexander; Hussels, Stephanie (Taylor & Francis, 2025)
Scholars have observed that management research can miss opportunities to translate its findings into practice. Some emphasize the importance of academic-practice collaboration in designing, implementing, and disseminating management research to ensure academic rigor and practitioner relevance. These views align well with evidence-based management perspectives. This paper's objective aims to describe what a research-to-practice translation path might resemble. This effort describes a six-step model to bridge research and practice: 1) identification, 2) engagement, 3) dissemination, 4) exploitation, 5) evaluation, and 6) refresh. It draws on diverse sources of information obtained via purposeful sampling (literature, websites, thought leader interviews, and personal experience and networks) to provide illustrative examples to reflect how researchers or practitioners who translate their Ph.D. work into practice engage with these steps. This work's contributions involve a roadmap for translation and extension of prior works in the extant literature calling for academic-practice collaboration in designing, implementing, and disseminating management research and multiple research-to-practice experience examples to illustrate how scholars and practitioners embrace such efforts for each phase. It also extends the ongoing academic conversation on this topic. This work proposes avenues for future research to address the limitations of this descriptive narrative. It seeks to refine the proposed model that can aid management researchers in their efforts to translate their works for managers and other practitioners.
Keywords: Entrepreneurship research; Evidence-based management; Practice application; Translation to practice; Entrepreneurship research; management research; evidence-based management; practice application; translation to practice; Business; Entrepreneurship and Small Business Management; Entrepreneurship; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 3507 Strategy, management and organisational behaviour